2017
DOI: 10.21053/ceo.2016.00031
|View full text |Cite
|
Sign up to set email alerts
|

Normative Hearing Threshold Levels in Koreans with Normal Tympanic Membranes and Estimated Prevalence of Hearing Loss

Abstract: Objectives We investigated the normative data on the hearing threshold levels of Koreans with normal tympanic membranes and the prevalence of hearing loss (HL) and nonserviceable hearing using the data from the Korea National Health and Nutrition Examination Surveys (KNHANES) during 2010–2012.Methods Data obtained from 16,673 participants ≥12-year-of-age with normal tympanic membranes who completed audiometric testing. We defined HL as the pure tone average (PTA) >25 dB hearing level at 500, 1,000, 2,000, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…Numerous studies investigating a pathophysiology and treatment for HL are being published and reported with increasing prevalence of HL. However, many of the studies had limitations to estimate the degree of HL for a certain period or to determine what characteristics affected hearing . It is meaningful that this study was designed with a longitudinal scheme, and the data was obtained from general population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies investigating a pathophysiology and treatment for HL are being published and reported with increasing prevalence of HL. However, many of the studies had limitations to estimate the degree of HL for a certain period or to determine what characteristics affected hearing . It is meaningful that this study was designed with a longitudinal scheme, and the data was obtained from general population.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of patients with HL is widely thought to result from the increase of an older population due to the extension of an individual's lifespan. A recent study using the Korean National Health and Nutrition Examination Survey from 2010 to 2012 suggested that the prevalence of HL in the 60s and 70s age groups was 49% and 75%, respectively . However, the prevalence of patients with HL has increased even in the relatively younger generation, especially in the 40s age group (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-sectional studies on ARHL have been conducted in Korea; however, these studies had a tangible limitation in that it was infeasible to identify changes in hearing ability in a single individual over a specific period. 3,4 To overcome this limitation, qualified longitudinal studies were conducted. Nevertheless, those investigations also had shortcomings; (1) some were performed only on subjects in particular occupations 9-12 ; (2) subjects’ hearing levels were assessed by self-reporting, not PTA 12 ; (3) some focused on risk factors other than aging, such as smoking, central adiposity, and poorly controlled DM in the Beaver Dam Eye Study 8 ; and (4) most studies were published quite a long time ago and did not reflect changes in people’s environment and lifestyle, for instance, the decrease of occupational noise exposure and the increase of vulnerability to other sound sources including music concerts, film theaters, and portable audio devices.…”
Section: Introductionmentioning
confidence: 99%